Simulators Usage Analysis to Estimate Power Consumption in Cloud Computing Environments - Meyer, Vinícius; Krindges, Rafael; Ferreto, Tiago C.; De Rose, Cesar A. F.; Hessel, Fabiano (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2018)
Cloud computing is one of the most popular technologies since it offers many benefits to IT companies around the world. However, cloud providers are facing increasing demand for computing services and requiring more and more power consumption. This paper evaluates the power consumption in large data centers through the use of cloud computing simulators, with various resources arrangements and how they impact on total power consumption. The results demonstrate how simulators could estimate energy costs for different types of infrastructures. Furthermore, we present an analysis of hardware utilization during the simulators execution.